2015
DOI: 10.1007/s13369-015-1702-1
|View full text |Cite
|
Sign up to set email alerts
|

Biosorption and Bioaccumulation of Copper and Lead by Heavy Metal-Resistant Fungal Isolates

Abstract: Microorganisms play an important role in the bioremediation of heavy metal-contaminated wastewater and soil. In this research, isolation of heavy metal-resistant fungi was carried out from wastewater-treated soil samples of Hudiara drain, Lahore. The purpose of the present investigation was to observe fungal absorption behavior toward heavy metal. The optimum pH and temperature conditions for heavy metal removal were determined for highly tolerant isolates of Aspergillus spp. along with the initial metal conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(59 citation statements)
references
References 28 publications
5
44
0
5
Order By: Relevance
“…Our results found that the sorption capacity increased and reached to the saturation value as the initial Cu +2 concentration increased in aqueous solution suggesting saturation kinetics with respect to Cu +2 concentration. This result was similar with the results of Iram and Abrar (2015) who observed that by using of Aspergillus flavus and Aspergillus niger biomass as biosorbents, Cu +2 uptake was increased by increasing of initial Cu + 2 concentration in aqueous medium. Mukhopadhyay et al (2007) and Sheng et al (2007) illustrated that, at high metal ion concentration, the number of ions adsorbed is more than at low metal concentration, where more binding sites were free for interaction.…”
Section: Discussionsupporting
confidence: 91%
“…Our results found that the sorption capacity increased and reached to the saturation value as the initial Cu +2 concentration increased in aqueous solution suggesting saturation kinetics with respect to Cu +2 concentration. This result was similar with the results of Iram and Abrar (2015) who observed that by using of Aspergillus flavus and Aspergillus niger biomass as biosorbents, Cu +2 uptake was increased by increasing of initial Cu + 2 concentration in aqueous medium. Mukhopadhyay et al (2007) and Sheng et al (2007) illustrated that, at high metal ion concentration, the number of ions adsorbed is more than at low metal concentration, where more binding sites were free for interaction.…”
Section: Discussionsupporting
confidence: 91%
“…These anionic cell walls can fix metals, and provide sites for nucleation and growth of minerals. This property has been the basis for many heavy metal removal studies using bacterial biomass [9]. The walls of gram-positive bacteria are efficient metal chelators.…”
Section: Discussionmentioning
confidence: 99%
“…This implies that the removal mechanism is not metabolically controlled. In contrast, the term bioaccumulation describes an active process whereby removal of metals requires the metabolic activity of a living organism [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…After 48 h, the fungal biomass was separated from medium using filtered through Whattman filter paper. The biomass was dried by the process of drying on hot oven in order to absorb the moisture content at temperature of 120°C for about 3-4 days and was utilized in further biosorption studies [26]. …”
Section: Preparation Of Dead Fungal Biomassmentioning
confidence: 99%